Climbers’ Perception of Hold Surface Properties: Roughness Versus Slip Resistance - Fuss, Franz Konstantin; Weizman, Yehuda; Niegl, Günther; Tan, Adin Ming (Frontiers in Psychology, 2020)
Climbers apply different amounts of friction to a climbing hold surface, depending on their performance. The aim of this research was to investigate how the properties of a hold’s surface are perceived and how the perception relates to the amount of friction applied to the hold. The holds’ surface properties are roughness/smoothness and grippiness/slippiness. 14 different surfaces with a wide range of property combinations were selected and placed on an instrumented climbing hold, mounted on a bouldering wall and incorporated into a climbing route. 22 climbers participated in the study. The ratio of friction to normal force (denoted friction coefficient or COF subsequently) was obtained from the sensor data; and the subjective ranking of the surface properties was provided by the participants. The average COF applied to the surfaces ranged from 0.53 (Teflon) to 0.84 (rubber). The surfaces with the lowest and highest grippiness and roughness ranking were Teflon and sandpaper, respectively. The correlation between roughness and COF was insignificant, whereas the correlation of grippiness and COF was significant. This applies to the 22 participants at the group level. At the individual level, 50% (11 climbers) of the participants did not show any correlations between surface properties and COF; 8 climbers exhibited correlations between the combined grippiness and roughness (multiple regression) and COF; and grippiness and COF; only one climber showed an additional correlation between roughness and COF. The results are interpreted in a way that climbers assess a hold’s surface based on the grippiness, and not on the roughness, and apply a COF to the hold that reflects the grippiness perception.